Ethnobotany evolution of a discipline - Schultes, Richard Evans; Von Reis, Siri 1931- (Portland, Oregon Dioscorides Press, 1995)
Ethnobotany: Evolution of a Discipline is a seminal volume, published on the 100th anniversary of this fascinating science, celebrating its recent evolution and providing a comprehensive summary of the history and current state of the field. It brings a broad and fully interdisciplinary approach to the study of human evaluation and use of plant materials in primitive or unlettered societies. The contributors of the thirty-six articles represent a broad spectrum of academic and scientific skill, as well as an international perspective. The editors are world-renowned ethnobotanists, and the range of carefully selected articles (most of them written specifically for this book) presents a truly global perspective on the theory and practice of today's ethnobotany. Although rooted in antiquity, ethnobotany is a dynamic contemporary science with tremendous importance for the future. The diminishing rain forests may well hold unknown keys to conquering devastating new diseases, and peoples native to those regions can often lead the way with their herbal knowledge. Experimentation with as-yet-unstudied plants may provide new solutions to expand food and energy reserves for our overpopulated planet. This volume offers important new material for those who work in fields of science devoted to plants, people, or both - including anthropology, archaeology, botany, environmental conservation, ethnopharmacology, geography, history, medicine, psychology, religion, and sociology. It is fascinating information for the general lay reader as well. Considering the impact of plant use throughout history in the human social structures of economics, politics, religion, and science, this is a book that contributes immeasurably to our understanding of human history and the world today.
The Scope and Aims of Ethnobotany in a Developing World / Janis B. Alcorn -- Ethnobotany: An Old Practice, A New Discipline / E. Wade Davis -- Ethnobotanical Method and Fact: A Case Study / Frank J. Lipp -- Ethnobotany Today and in the Future / Ghillean T. Prance -- Ethnobotany and Phytoanthropology / Priyadarsan Sensarma and Ashoke K. Ghosh -- New Paradigms for a New Ethnobotany: Reflections on the Case of Mexico / Victor Manuel Toledo -- Art and Artifact as Ethnobotanical Tools in the Ancient Near East with Emphasis on Psychoactive Plants / William A. Emboden, Jr. -- "This Little Book of Herbs": Psychoactive Plants as Therapeutic Agents in the Badianus Manuscript of 1552 / Peter T. Furst -- Gods and Plants in the Classical World / Carl A.P. Ruck -- The Importance of Ethnobotany for Tropical Forest Conservation / Mark J. Plotkin -- Quantitative Ethnobotany and the Case for Conservation in Amazonia / G.T. Prance, W. Balee, B.M. Boom and R.L. Carneiro.
Includes bibliographical references and index.
Keywords: Ethnobotany